FOOD SAFETY AND VETERINARY LEGISLATION COMPARISON WITH ACQUIS - Thomaj, Eneida (European Scientific Journal, ESJ, 2015)
This paper discusses food safety and veterinary service legislation in Albania and their degree of the approximation with the EU legislation. This paper also covers a description of the competent authorities in Albania, empowered with inspections and monitoring duties of the market but also with tools for providing adequate response to eventual emergencies. The paper underlines the outcome of the latest Progress Report on Albania, especially with regard to the building capacity of the competent authorities and further approximation of the domestic legislation with the acquis communautaire obligations of the Republic of Albania in view of the provisions of the Stabilization and Association Agreement. At the end, the paper gives conclusion as per the deficiencies that are observed in the enforcement of the provisions of the legislation.